CD166-mediated epidermal growth factor receptor phosphorylation promotes the growth of oral squamous cell carcinoma. (August 2016) - Jia, Guodong; Wang, Xu; Yan, Ming; Chen, Wantao; Zhang, Ping
Highlights: Identifying EGFR as a potential CD166 interaction protein, and a subsequent endogenous co-IP assay confirmed this interaction. Finding that CD166 significantly enhanced EGFR phosphorylation and prolonged EGF/EGFR signalling pathway activation. Pinpointing the CD166 as an intriguing therapeutic target for patients suffered from oral squamous cell carcinoma. Summary: CD166 has been considered a relatively specific marker of stem cells and cancer stem cells, and the altered expression of CD166 has also been reported as a prognostic marker of several other types of cancer. However, the molecular functions of CD166 in these cancer cells are largely unknown. In this study, we found that CD166 significantly enhanced epidermal growth factor receptor (EGFR) phosphorylation and prolonged epidermal growth factor (EGF)/EGFR signalling activation. In addition, EGF stimulation in CD166-overexpressing oral squamous carcinoma cells led to enhanced colony formation, invasion capacity and cytoskeletal re-organization in vitro and elevated tumourigenesis in vivo . Taken together, the results of our study identify CD166 as an intriguing therapeutic target for patients suffering from oral squamous cell carcinoma (OSCC).